1962
DOI: 10.1063/1.1728809
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Moments of Intermetallic Compounds of Transition and Rare-Earth Elements

Abstract: The effect of adding the rare-earth elements to cobalt, iron, and nickel has been investigated. Antiferromagnetic coupling was found to exist in the cobalt and iron rare-earth compounds. The moment per formula unit of the compound Co5Y is increased when Sm, Pr, and Nd are substituted for yttrium and decreased when Tm, Gd, Tb, Er, Dy, and Ho are substituted. This is explained on the basis that although the spin moments of cobalt and rare earths are coupled antiferromagnetically in these compounds, the orbital m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…The heat capacity of CeNi 2 and CeNi 5 at 0-300 K was reported by Marzouk et al [7] and Wallace [8]. Based on these works [7][8][9][10][11][12][13][14][15][16][17][18][19][20], the Ce-Ni system was reviewed by Nash and Tung [21]. They stated that some uncertainties in the Ce-Ni system should be resolved.…”
Section: Experimental Informationmentioning
confidence: 93%
See 1 more Smart Citation
“…The heat capacity of CeNi 2 and CeNi 5 at 0-300 K was reported by Marzouk et al [7] and Wallace [8]. Based on these works [7][8][9][10][11][12][13][14][15][16][17][18][19][20], the Ce-Ni system was reviewed by Nash and Tung [21]. They stated that some uncertainties in the Ce-Ni system should be resolved.…”
Section: Experimental Informationmentioning
confidence: 93%
“…The magnetic contribution to the Gibbs energy mg G Ce m Ni n m is included in the Gibbs energy G Ce m Ni n m , because these intermetallic compounds are nonmagnetic and the critical temperatures of magnetic transformation are much below 298.15 K [8][9][10][11].…”
Section: Stoichiometric Intermetallic Compoundsmentioning
confidence: 99%
“…The analysis of its magnetic properties shows that the Curie temperatures are very low. The highest value of T C was evidenced for GdNi 5 compound [1][2][3][4] which was obtained for the first time in 1962 by Nesbitt et al [6]. Latter studies showed that GdNi 5 is the ferrimagnet below T C = 32 K and the value of magnetization extrapolated to 0 K equals 6.2 µ B /f.u.…”
Section: Introductionmentioning
confidence: 88%
“…The RT 5 compounds, where R is rare earth and T is a transition metal, show very interesting magnetic properties due to the combination of 3d itinerant and 4f localized magnetism [1][2][3][4][5][6][7][8][9][10][11]. One of the most known series is RNi 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The RNi 5 compounds (R = rare earth) have been intensively studied in recent decades [1][2][3][4][5][6][7][8][9][10][11][12]. Newly obtained series of the Yb x Gd 1−x Ni 5 compounds (x ≤ 0.5) exhibit interesting properties [5].…”
Section: Introductionmentioning
confidence: 99%